A 125 μW , Fully Scalable MPEG-2 and H.264 - Liu, T.-M (IEEE Journal of solid state circuits)
A low-power dual-standard video decoder has been developed for mobile applications. It supports MPEG-2 SP@ML and H.264/AVC BL@L4 video decoding in a single chip and features a scalable architecture to reach area/power efficiency. This chip integrates diverse algorithms of MPEG-2 and H.264/AVC to reduce silicon area. Three low-power techniques are proposed. First, a domain-pipelined scalability (DPS) technique is used to optimize the pipelined structure according to the number of processing cycles. Second, bandwidth scalability is implemented via a line-pixel-lookahead (LPL) scheme to improve the external bandwidth and reduce the internal memory size, leading to 51% of memory power reduction compared to a conventional design. Third, low-power motion compensation and deblocking filter are designed to reduce the operating frequency without degrading system performance. A test chip is fabricated in a 0.18mum one-poly six-metal CMOS technology with an area of 15.21 mm2. For mobile applications, H.264/AVC and MPEG-2 video decoding of quarter-common intermediate format (QCIF) sequences at 15 frames per second are achieved at 1.15 MHz clock frequency with power dissipation of 125 muW and 108 muW, respectively, at 1V supply voltage